Influence of Capital Structure, Capital Expenditure , and Firm Size on Firm Value with Profitability as Intervening Variable - Zefriyenni -; Nila Pratiwi; Rahma Fitria Sari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the major impacts of Capital Structure, Capital Expenditure and Firm Size on Company Value using Profitability as an Intervening Variable in Manufacturing Companies listed on the IDX for the 2016-2020 period. The population in this study amounted to 195 manufacturing companies and a sample of 60 companies using purposive sampling technique. This study used SPSS software version 25. Using the results of this study it was concluded that: (1) there is a significant influence between capital structure and profitability. (2) there is no effect between Capital Expenditure on Profitability. (3) there is no influence between Firm Size on Profitability. (4) there is a significant impact between capital structure and firm value. (5) there is no impact between Capital Expenditure on Company Value. (6) there is a significant effect between Firm Size and Firm Value. (7) there is a significant impact between Profitability on Firm Value. (8) Profitability is able to moderate the correlation between capital structure and firm value. (9) Profitability is not able to moderate the correlation between Capital Expenditure on Firm Value. (10) Profitability is unable to moderate the relationship between Firm Size and Firm Value. Keywords: Capital Structure, Capital Expenditure , Firm Size , Firm Value, Profitability